Preclinical Development of a Lentiviral Vector for Gene Therapy of X-Linked Severe Combined Immunodeficiency - Valentina Poletti; Sabine Charrier; Guillaume Corre; Bernard Gjata; Alban Vignaud; Fang Zhang; Michael Rothe; Axel Schambach; H. Bobby Gaspar; Adrian J. Thrasher; Fulvio Mavilio (Molecular Therapy: Methods & Clinical Development, 2018)
X-linked severe combined immunodeficiency (SCID-X1) is caused by mutations in the interleukin-2 receptor γ chain gene (IL2RG), and it is characterized by profound defects in T, B, and natural killer (NK) cell functions. Transplantation of hematopoietic stem/progenitor cells (HSPCs) genetically corrected with early murine leukemia retrovirus (MLV)-derived gammaretroviral vectors showed restoration of T cell immunity in patients, but it resulted in vector-induced insertional oncogenesis. We developed a self-inactivating (SIN) lentiviral vector carrying a codon-optimized human IL2RG cDNA driven by the EF1α short promoter (EFS-IL2RG), and we tested its efficacy and safety in vivo by transplanting transduced Il2rg-deficient Lin− HSPCs in an Il2rg−/−/Rag2−/− mouse model. The study showed restoration of T, B, and NK cell counts in bone marrow and peripheral blood and normalization of thymus and spleen cellularity and architecture. High-definition insertion site analysis defined the EFS-IL2RG genomic integration profile, and it showed no sign of vector-induced clonal selection or skewing in primarily and secondarily transplanted animals. The study enables a phase I/II clinical trial aimed at restoring both T and B cell immunity in SCID-X1 children upon non-myeloablative conditioning. Keywords: gene therapy, immunodeficiency, SCID-X1, lentiviral vector, integration, genotoxicity